Segmented Iba1-Positive Processes of Microglia in Autism Model Marmosets - Sanagi, Tomomi; Sasaki, Tetsuya; Nakagaki, Keiko; Minamimoto, Takafumi; Kohsaka, Shinichi; Ichinohe, Noritaka (Frontiers in Cellular Neuroscience, 2019)
Autism spectrum disorder (ASD) is one of the most widespread neurodevelopmental disorders, characterized by impairment in social interactions and restricted stereotyped behaviors. Using immunohistochemistry and positron emission tomography (PET), several studies have provided evidence of the existence of activated microglia in ASD patients. Recently, we developed an animal model of ASD using the new world monkey common marmoset (Callithrix jacchus) and demonstrated ASD-like social impairment after the in utero administration of valproic acid (VPA). To characterize microglia in this marmoset model of ASD from early toddler to adult, morphological analyses of microglia in VPA marmosets and age-matched unexposed (UE) marmosets were performed using immunohistochemistry for microglia-specific markers, Iba1 and P2RY12. The most robust morphological difference between VPA marmosets and UE marmosets throughout the life span evaluated were the microglia processes in VPA marmosets being frequently segmented by thin and faintly Iba1-positive structures. The segmentation of microglial processes was only rarely observed in UE marmosets. This feature of segmentation of microglial processes in VPA marmosets can also be observed in images from previous studies on ASD conducted in humans and animal models. Apoptotic cells have been shown to have segmented processes. Therefore, our results might suggest that microglia in patients and animals with ASD symptoms could frequently be in the apoptotic phase with high turnover rates of microglia found in some pathological conditions.